Functionalized biomimetic nanoparticles loaded with salvianolic acid B for synergistic targeted triple-negative breast cancer treatment - Nuo Cheng; Qianqian Zhou; Zongfang Jia; Yang Mu; Sheng Zhang; Lei Wang; Yunna Chen (Materials Today Bio)
The therapeutic effect of immune checkpoint inhibitors (ICIs) in triple-negative breast cancer (TNBC) is unsatisfactory. The immune ''cold'' microenvironment caused by tumor-associated fibroblasts (TAFs) has an adverse effect on the antitumor response. Therefore, in this study, mixed cell membrane-coated porous magnetic nanoparticles (PMNPs) were constructed to deliver salvianolic acid B (SAB) to induce an antitumor immune response, facilitating the transition from a ''cold'' to a ''hot'' tumor and ultimately enhancing the therapeutic efficacy of immune checkpoint inhibitors. PMNP-SAB, which is based on a mixed coating of red blood cell membrane and TAF membrane (named PMNP-SAB@RTM), can simultaneously achieve the dual effects of ''immune escape'' and ''homologous targeting''. Under the influence of an external magnetic field (MF), SAB can be targeted and concentrated at the tumor site. The SAB released in tumors can effectively inhibit the production of extracellular matrix (ECM) by TAFs, promote T-cell infiltration, and induce antitumor immune responses. Ultimately, the combination of PMNP-SAB@RTM and BMS-1 (PD-1/PD-L1 inhibitor 1) effectively inhibited tumor growth. Finally, this study presents a precise and effective new strategy for TNBC immunotherapy on the basis of the differentiation of ''cold'' and ''hot'' microenvironments.